Radial Optic Neurotomy for Central Retinal Vein Occlusion - Alireza Ramezani (Journal of Ophthalmic & Vision Research, 2009)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!--[if gte mso 10]> <style>
/* Style Definitions */
table.MsoNormalTable
{mso-style-name:"Table Normal";
mso-tstyle-rowband-size:0;
mso-tstyle-colband-size:0;
mso-style-noshow:yes;
mso-style-parent:"";
mso-padding-alt:0cm 5.4pt 0cm 5.4pt;
mso-para-margin:0cm;
mso-para-margin-bottom:.0001pt;
mso-pagination:widow-orphan;
font-size:10.0pt;
font-family:"Times New Roman";
mso-ansi-language:#0400;
mso-fareast-language:#0400;
mso-bidi-language:#0400;}
</style> <![endif]--> When several and very different treatment modalities exist for one ailment, it usually means that none of them is generally effective or superior to others. Central retinal vein occlusion (CRVO) is a condition for which various types of management have been proposed. However, the only standard care suggested by the Central Vein Occlusion Study Group (CVOSG) is panretinal photocoagulation when the condition is complicated by iris neovascularization. In 2001, radial optic neurotomy (RON) was suggested by Opremcak for treatment of CRVO. This therapeutic modality has raised much debate among authorities. Herein, we present the opposing views of two vitreoretinal specialists regarding this issue.